EFFECT OF POMEGRANATE EXTRACT AND ITS NANOPARTICLES ON HUMAN TONGUE SQUAMOUS CELL CARCINOMA CELL LINE (Journal of Pharmaceutical Negative Results, 2023)
Aim: The present study would be directed to evaluate: The effects of Pomegranate Extracts (PE) and PE loaded with polyethylene glycol-poly lactic acid-co-glycolic acid (-PE-PEG-PLGA) on human tongue squamous cell carcinoma cell line.Methodology: The Human tongue carcinoma cell line (HNO-97) cells were propagated and maintained under basic culture media. Cells were grouped according to culture media to control group A and experimental groups (PE group (B1), PE - PEG-PLGA group (B2), was tested for cell viability, Bcl-2-associated X protein (BAX) expression, caspase-3 expression, and DNA fragmentation were all examined using (4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) real-time polymerase chain reaction (RT-PCR) and diphenylamine (DPA) respectively.Results: Regarding cell viability, a higher mean value at different concentrations was recorded in groups B2 and B1, respectively. In aspects of BAX expression, caspase-3 expression, and DNA fragmentation, groups B2, and B1, had higher mean values than control group A with a highly significant difference (p = 0.000). Regarding inhibitory concentration (IC50%) doses, a lower dose needed to show the same effect was recorded in groups B2 and B1(1.21ug/ml and 6.41ug/ml, respectively.Conclusions: The pomegranate plays a role in antitumor activity as alone or with nanoparticles.